THE ROLE OF QUILLBOT IN ENHANCING NARRATIVE WRITING SKILLS AMONG ELEVENTH GRADE STUDENTS - Syarani, Arinda; Rosmiyati, Evi; Hidayad, Ferri; Soudaphone Vongphachanh; Khamsavanh Phommasane (Universitas PGRI Palembang, 2025)
This study explored the impact of QuillBot, an AI-driven writing assistant, on improving the narrative writing abilities of eleventh-grade students at SMA Daarul Aitam Palembang. Writing narrative texts poses a significant challenge for English learners due to the complexities of grammar, vocabulary, and coherent idea development. Adopting a quantitative methodology, the research utilized a One-Group Pre-test Post-test Design involving 30 students who completed a narrative writing task titled “The Best Day Ever” both before and after the intervention. During the treatment phase, participants were trained in using various QuillBot features—such as paraphrasing, grammar correction, and vocabulary enhancement—to revise their work. The findings revealed a notable improvement in the average score, rising from 58.33 on the pre-test to 80.00 on the post-test. A paired sample t-test further validated the tool’s effectiveness, yielding a significance value of 0.000, well below the 0.05 threshold. These results suggest that QuillBot significantly aided students in minimizing grammatical mistakes, enriching their vocabulary, and structuring their ideas more effectively. Overall, the study underscores the potential of QuillBot as a supportive resource in English writing instruction, particularly within EFL learning environments.